On all fronts: EOKA and the Cyprus insurgency, 1955-1959 - Novo, A (2010)
Abstract Thesis Title: On All Fronts: Cyprus and the EOKA Insurgency, 1955-1959 Andrew Novo, St. Antony’s College Submitted in Hilary Term 2010 to satisfy the requirements of a DPhil in Modern History On All Fronts is a thesis focused on the EOKA insurgency in Cyprus (1955-1959), which aimed at overturning British rule and unifying the island with Greece. EOKA’s campaign was one of several insurgencies carried out against Britain in the two decades following the Second World War. This allowed British policymakers and soldiers to apply lessons learned in other colonies on the island. These lessons included pursuing a political solution in tandem with military operations, unifying command and control, improving intelligence capabilities, and increasing the number of police and soldiers on the ground. Cyprus also presented distinctive challenges. The insurgency was not inspired by communism, like many other anti-colonial struggles, but by right-wing nationalism. The campaign was also intimately linked to the strategic reorganisation undertaken by Britain after 1945. Retreat from India and Palestine increased the importance of the Middle East and Africa, making a presence in Cyprus central to Britain’s post-war plans. Finally, Cypriot demographics meant that the island’s Turkish minority (some eighteen percent) – supported by Ankara – opposed union with Greece. An ethnic-based civil war on the island was possible, as was a regional war between Greece and Turkey. British policy sought to avoid both of these potential conflicts while maintaining the strength of NATO and positive relations with both Athens and Ankara. Utilizing newly declassified papers from the British government, in conjunction with evidence from Greek-Cypriot sources, this study offers insights into the campaign from the perspective of both insurgent and counter-insurgent forces. Parallel to the military analysis, the thesis addresses the political aspect of the insurgency, demonstrating the deep connection in insurgency war between military operations and diplomatic negotiation. While counter-insurgency operations failed to destroy EOKA, the success of government forces created pressure for a diplomatic solution and highlighted the reality that there were insurmountable military and strategic obstacles to union with Greece.